Faktor-Faktor Yang Mempengaruhi Rendahnya Kunjungan Antenatal Care Pada Trimester Pertama Di Puskesmas Pagurawan Kabupaten Batubara Tahun 2022 - Anna Waris Nainggolan; Parningotan Simanjuntak; Nopalina Suyanti Damanik; Astaria Br. Ginting; Ribur Sinaga; Flora Sinaga; Imarina Tarigan (Jurnal Kesehatan dan Fisioterapi, 2022)
In Batubara Regency the coverage of K1 is 87.10% in 2019 and K4 is 73.32%. In Pagurawan Health Center the K1 coverage in 2019 is 63% while the expected target is 95%. From these data, it is known that the coverage of K1 antenatal care in the Pagurawan Health Center area is still low and has not yet reached the national target. This study aims to determine the factors that influence the low antenatal care visits in the first trimester at the Pagurawan Health Center, Batubara Regency in 2022. This type of research is an analytical observational study using a Cross-Sectional approach, namely to analyze the Factors Affecting the Low Antenatal Care Visits in First Trimester at Pagurawan Health Center. The population in this study were all pregnant women who had passed the first trimester and were willing to be interviewed. The total population obtained is 153 people. Samples were taken by stratified random sampling as many as 81 people. Data analysis technique using chi-square. The variables of knowledge, education, attitude, and parity are variables related to the first Antenatal Care (ANC) visit at the Pagurawan Health Center, Kec. Medang Deras Batubara Regency in 2022. Age and attitude of health workers are variables that are not related to the first Antenatal Care (ANC) visit at the Pagurawan Health Center, Kec. Medang Deras, Batubara Regency in 2022. It is recommended to health workers at Pagurawan Health Center, especially midwives at Pagurawan Health Center, to provide counseling to pregnant women and husbands about the importance of prenatal care.Keywords: knowledge, education, attitude, ANC